Pengembangan Modul Literasi Numerasi Berbasis Konteks Budaya Lokal Untuk Siswa SMP Negeri 3 Palopo - Aura Negarawan; Rio Fabrika Pasandaran; Karmila Karmila (Venn: Journal of Sustainable Innovation on Education, Mathematics and Natural Sciences, 2026)
The low ability of students' numeracy literacy, students' difficulties in applying mathematical concepts to various problems, and the lack of integration of local culture in teaching materials cause mathematics learning to feel abstract and less meaningful for students. This type of research is a development research (Research and Development) which aims to determine the process and results of developing a valid, practical, and effective numeracy literacy teaching module based on local cultural context for class VIII students of SMP Negeri 3 Palopo. The development model used is the 4-D model which includes the stages of defining, designing, developing, and disseminating. The instruments used are the teaching module validation sheet, student response questionnaire, observation sheet, and numeracy literacy ability test. The results of the limited trial show that (1) the average result of the validity of the teaching module is 3.1 with a valid category; (2) the results of the practicality test of the teaching module include an average student response of 83.63%, an average learning implementation of 94.56%, and an average student activity of 85.09%; and (3) the results of the effectiveness test of the teaching module as seen from the percentage of students' completion of the numeracy literacy test results of 74.07% with an effective category. Based on the results of this study, the numeracy literacy teaching module based on the local cultural context that was developed meets the requirements of being valid, practical, and effective.